Photovoltaic flyback micro-inverter with power decoupling technique - Salam Jabr; Adel A. Obed (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper proposes a low-cost single-phase micro-inverter for grid-connected photovoltaic (PV) system. The lifetime of the conventional flyback micro-inverter is shortened, because lifetime of a large electrolyte capacitor is shortened. For this reason, the need for a large electrolyte capacitor is avoided by proposing power decoupling (PD) circuit. Dual advantages are achieved by proposed circuit, first high-power decoupling with small capacitances and other to protect the main MOSFET from spike voltage stress during turn off time without needing for additional a snubber circuit. Consequently, PD circuit is already used as a snubber circuit to absorb the leakage energy in the transformer which may destroy the switch and thus the voltage spike on the main MOSFET decreased. In addition, operating principle, modes, and control scheme of the proposed micro-inverter are discussed. As the simulation results, the input power ripple of the single-phase power fluctuation is under than 4%, unity power factor (P.F) and the total harmonic distortion (THD) of the proposed inverter output current is less than 5%. PSIM tool box is provided to simulate the proposed system and the simulation results are adequate.